2022
DOI: 10.28918/jief.v2i1.5327
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pergantian CEO dan Pengungkapan CSR sebagai Maslahat Mursalah terhadap Manajemen Laba dengan Struktur Corporate Governance sebagai Variabel Moderasi

Abstract: This study aims to determine whether CEO turnover and CSR disclosure as maslahat mursalah are moderated by corporate governance structure consisting of independent commissioners, audit committee and institutional  ownership partially affect earnings management. This study uses secondary data from manufacturing companies during 2019. Sampling technique using purposive sampling. The data were collected and analyzed using moderated regression analysis (MRA). The result indicate that CEO turnover and CSR disclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Effendi et al (2019) [4] And Gurusinga et al (2023) [5] also stated that there was a positive influence between CEO change on earnings management, but it was not significant because CEO change gave a signal that there would be changes in company management by establishing new policies or regulations to improve company performance so that earnings management practices could be minimized. However, this is different from the research conducted by Prawestri et al (2022) [6] found that CEO turnover does not affect earnings management. This is because changing CEOs in a company is a natural thing to happen for various reasons, such as the end of their term of office, entering retirement, or passing away while in office.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Effendi et al (2019) [4] And Gurusinga et al (2023) [5] also stated that there was a positive influence between CEO change on earnings management, but it was not significant because CEO change gave a signal that there would be changes in company management by establishing new policies or regulations to improve company performance so that earnings management practices could be minimized. However, this is different from the research conducted by Prawestri et al (2022) [6] found that CEO turnover does not affect earnings management. This is because changing CEOs in a company is a natural thing to happen for various reasons, such as the end of their term of office, entering retirement, or passing away while in office.…”
Section: Introductioncontrasting
confidence: 98%
“…New CEOs tend to use the practice of taking a bath to demonstrate better performance and gain investor support. However, research by Prawestri et al, (2022) [6] shows that a change in CEO has no effect on earnings management practices in the company. CEO changes are not always motivated by negative things, but can also be caused by various non-economic reasons such as death, end of term of office, or retirement.…”
Section: Hypothesis Development 271 the Effect Of Ceo Change On Earni...mentioning
confidence: 99%